Successful endoscopic treatment of an intraductal papillary neoplasm of the bile duct - Natov, Nikola S (World J Gastrointest Endosc, 2017)
We present a case of a 76-year-old man with right upper quadrant abdominal pain and weight loss, who was found to have an intraductal papillary neoplasm of the bile duct (IPNB) of the pancreaticobiliary subtype, deemed curatively resectable. The patient declined surgery and opted for endoscopic therapy. He underwent two sessions of endoscopic retrograde cholangiopancreatography (ERCP)-guided radiofrequency ablation (RFA). Ten months later, no evidence of recurrence was identified on repeat ERCP. To our knowledge, this is the first reported case of successful use of RFA as a primary treatment modality for resectable IPNB.